Agreement. Central State University and the American Association of University Professors, Central State University Chapter. 1985-1988 - Central State Univ., Edmond, OK.; Central State Univ., Edmond, OK.; American Association of Univ. Professors, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
The collective bargaining agreement between Central State University and the university's chapter (295 members) of the American Association of University Professors (AAUP), covering the period 1985-1988, is presented. Items covered in the agreement include: academic freedom, nondiscrimination, affirmative action plans, maintenance of practices, institutional responsibilities, academic safeguards and responsibilities, faculty appointment and tenure policies and procedures, promotion and tenure, personnel files, professional and personal leaves of absence, court leave, military and political leave, sick leave, special or emergency leaves, special duty assignments, termination because of discontinuation of a department or program, termination for cause, provisions for emeriti, evaluations, workload, professional travel, parking, university governance, faculty representatives attendance at Board of Trustees meeting, the academic department, patents and copyrights, grievance and arbitration, across-the-board salary adjustments, minimum salaries, salary adjustments for years of service, compensation for overloads and summer school, initial salaries and ranks, medical/dental insurance, life insurance, disability insurance, retirement programs, appointment year and salary checks, rights and duties of the AAUP, and agreement management. AAUP grievance forms are appended. (SW)
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Freedom; Affirmative Action; Collective Bargaining; College Faculty; Contracts; Employment Practices; Faculty Evaluation; Faculty Promotion; Faculty Workload; Fringe Benefits; Grievance Procedures; Higher Education; Leaves of Absence; Personnel Policy; Program Termination; State Universities; Teacher Employment Benefits; Teacher Salaries; Tenure; Unions; AAUP Contracts -- Central State University OK; American Association of University Professors -- Disability Payments -- Personnel Files -- Union Rights; Legal/Legislative/Regulatory Materials